ISLAMIC IDENTITY NEGOTIATION IN RURAL SOCIETY OF BANGKA ISLAND : BETWEEN GLOBAL AND LOCAL - Ahmad Syarif Hidayatullah; Nur Fitriyana; Almunadi (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2025)
This ethnographic study examines how a traditional Muslim community in Payabenua village, Bangka Island, Indonesia, negotiates Islamic identity amid globalization. Drawing on nine months of fieldwork (2024), the research explores the interplay between local traditions, global Islamic symbols, and social pluralism. Using cultural hybridity theory (Bhabha), multiple modernities framework (Eisenstadt), and everyday pluralism concepts, the study reveals three key findings: (1) global Islamic architectural forms coexist with local traditions through strategic appropriation—the new Middle Eastern-style mosque amplifies rather than displaces the traditional nganggung ritual; (2) potentially controversial symbols like niqab gain acceptance through mediation by local religious authorities (guru kampung) who integrate them into Shafi'i jurisprudential frameworks; (3) everyday pluralism grounded in economic interdependence and ritual reciprocity remains resilient despite Islamic revivalism. The study contributes theoretically by extending hybridity theory to rural contexts, demonstrating Islamic modernity through tradition revitalization rather than replacement, and revealing practice-based pluralism's durability. Findings challenge narratives portraying Muslim communities as passive recipients of global influences, instead revealing active, creative negotiation processes that produce distinctive hybrid modernities simultaneously global and local, modern and traditional, revivalist and pluralist.